(untitled) (Texas Journal of Engineering and Technology, 2023)
The article analyzes the operating characteristics of a valve converter based on a series autonomous current inverter based on computer studies. It is shown that the valve converter circuit based on a series autonomous current inverter with a thyristor-choke compensating device not only provides the ability to regulate and stabilize the output parameters of the converter, but also helps to improve the dynamic properties of the converter due to the appearance of an additional recharging circuit for the switching capacitor. The obtained operating characteristics make it possible to determine the value of the control range that ensures stabilization of the output voltage while maintaining switching stability and, thereby, facilitates the determination of the optimal parameters of a valve converter based on a series autonomous current inverter